Peran Pembelajaran Berbasis Inkuiri, Efikasi Diri dan Kemandirian Belajar Sebagai Prediktor Kemampuan Berpikir Kritis Siswa - Laksono, Aura Dewi Amaryllis Adi; Gunawan, Diah Setyorini; Mayasari, Viviana (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This research aims to analyze the influences of inquiry-based learning, self-efficacy, and learning independence on students' critical thinking abilities within economics lessons. It seeks to provide new insights into the interaction of these factors in economics education, specifically exploring how tailoring inquiry-based learning can enhance critical thinking skills and contribute to more effective teaching methods.Method – The study employed a quantitative approach using survey methods for data collection. Data was gathered through distributing questionnaires via Google Forms, conducting student interviews, and administering objective tests that included essay questions to assess critical thinking abilities. The sampling technique used was simple random sampling. Data analysis included instrument testing, classical assumption testing, and multiple linear regression analysis. Findings – The findings of this research indicate that all three variables—inquiry-based learning, self-efficacy, and learning independence—have a significant positive effect on students' critical thinking abilities, as evidenced by the significance values for each variable being below 0.5. Specifically, the study found that inquiry-based learning has a positive effect, self-efficacy positively influences, and learning independence has a beneficial impact on students' critical thinking abilities. Furthermore, the Adjusted R Square value of 0.555 suggests that these three variables collectively account for 55.5% of the influence on critical thinking abilities. Research Implications – The findings imply that strengthening inquiry-based learning, together with enhancing students’ self-efficacy and learning independence, can serve as an effective strategy for designing economics curricula and instructional practices that foster students’ critical thinking abilities.